Target-capture full-length double-stranded cDNA long-read sequencing through Nanopore revealed novel intron retention in patient with tuberous sclerosis complex - Ura, Hiroki; Togi, Sumihito; Niida, Yo (Frontiers in Genetics, 2023)
Tuberous sclerosis complex (TSC) is a relatively common autosomal dominant disorder characterized by multiple dysplastic organ lesions and neuropsychiatric symptoms, caused by loss-offunction mutation of either TSC1 or TSC2. The genetic diagnosis of inherited diseases including TSC in the clinical field is widespread using next-generation sequencing (NGS). The mutations in proteincoding exon tend to be verified because mutation directly cause abnormal protein. However, it is relatively difficult to verify the mutations in intron region because it is required to investigate whether the intron mutations affect the abnormal splicing for transcripts. In this study, we developed the target-capture full-length double-stranded cDNA sequencing using long-read sequencer Nanopore (Nanopore Long-read Target Sequencing). This method revealed that the intron mutation in TSC2 gene and that the intron mutation produces the novel intron retention splicing transcripts which generate the truncated proteins. The protein-coding transcripts were decreased due to the expression of the novel intron retention transcripts, which will cause TSC in the patient with the intron mutation. Our results indicate that the Nanopore Long-read Target Sequencing is useful for the detection of mutations and confers information on the full-length alternative splicing transcripts for the genetic diagnosis.